A salt corrosion resistant admixture for marine engineering concrete and preparation method thereof

By using salt-resistant corrosion admixture composed of various raw materials such as resists and anti-seepage agents in offshore concrete, the problem of salt-erosion in marine environments is solved, and the effect of high strength and excellent durability is achieved.

CN118930125BActive Publication Date: 2025-04-25RIZHAO HAIGONGYAN NEW MATERIALS CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411085645.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2025-04-25
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

Offshore concrete faces salt erosion problems in marine environments. The existing anti-seepage and corrosion-resistant admixtures are not ideal, and may lead to a reduction in other properties of concrete and affect durability.

Method used

The anti-salt-resistant corrosion admixture for marine concrete consisting of resists, anti-seepage agents, mineral powders, fillers, resist additives and water reducers is used to improve the density and corrosion resistance of concrete through the combination of various raw materials.

Benefits of technology

It significantly improves the early and late strength of offshore concrete, has excellent durability, reduces the risk of salt corrosion, and extends the service life of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a salt corrosion resistant admixture for marine engineering concrete and a preparation method thereof, and belongs to the technical field of concrete admixture. It is composed of the following raw materials in parts by weight: 40-60 parts of corrosion resistant agent, 20-30 parts of impermeable agent, 60-80 parts of mineral micropowder, 0.5-1 parts of filler, 1-3 parts of corrosion resistant additive, and 0.3-0.5 parts of water reducing agent. The present invention uses a variety of raw materials to work together. On the one hand, from the perspective of improving the density of concrete, a variety of raw materials are blended and used, which can significantly improve the working performance of concrete and the internal density of concrete; on the other hand, part of the inhibitor material is added from the perspective of physical and chemical reactions, which can reduce the occurrence of corrosion reactions, thereby improving the ability of marine engineering concrete to resist harmful ions of salts in seawater such as chloride ions and sulfate ions from entering the interior of concrete, reducing the damage to marine engineering concrete specimens, and making marine engineering concrete have higher early and late strength and excellent durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete admixtures, and particularly relates to a salt corrosion resistant admixture for marine engineering concrete and a preparation method thereof. Background Art

[0002] There are an increasing number of infrastructure projects such as cross-sea bridges, cross-sea tunnels, and offshore deep-water ports connecting my country's coastal economic zones. For concrete structures in seawater environments, chloride ions and other components in seawater gradually penetrate into the concrete in a diffusion manner under the action of concentration gradients, reacting with the cementitious materials therein, causing concrete corrosion. At present, the salt corrosion faced by marine engineering concrete in the marine environment mainly includes chloride ion, sulfate ion, and magnesium ion corrosion. Seawater contains a large amount of chloride ions (Cl - ), these chloride ions pass through the pores and cracks of concrete through diffusion and penetration, and gather on the surface of steel bars. When the chloride ion concentration on the surface of steel bars reaches a certain value, Cl - It will react with C3A to form Friedel's salt, which will reduce the internal pH of concrete, destroy the passive film of steel bars, cause steel bars to rust, and then crack and damage the concrete structure. Sulfate ions react with hydration products in concrete to form expansive products, such as gypsum (CaSO4·2H2O) and calcium aluminate (AFt). The formation of these expansive products will cause the concrete volume to expand and crack, and in severe cases, even cause concrete spalling and structural damage. Seawater also contains a large amount of magnesium ions (Mg 2+ ), these magnesium ions react with the hydroxide ions (OH - ) reacts to form magnesium hydroxide, which is a white, soft, and indeterminate substance. It is easy to form expansive products inside the concrete, causing the concrete structure to be destroyed, thereby affecting the pore structure and mechanical properties of the concrete and reducing the density and strength of the concrete.

[0003] At present, there are two main measures to inhibit salt corrosion damage to marine concrete: one is to increase the density of concrete, thereby preventing various salt ions such as chloride ions, sulfate ions, and magnesium ions from the external environment from penetrating into the concrete; the other is to reduce the occurrence of physical and chemical reactions that generate corrosion products by adding certain types of ion corrosion inhibitors, thereby fundamentally reducing the risk of concrete being corroded by different salt ions. Although many different concrete anti-seepage and anti-corrosion admixtures have been disclosed in the prior art, most of the anti-seepage and anti-corrosion admixtures are not very ideal when facing a complex marine environment for a long time, and sometimes even lead to a reduction in other properties of concrete, which is not conducive to improving the durability of concrete. Therefore, there is an urgent need to develop a high-performance, high-stability anti-salt corrosion admixture suitable for marine concrete. Summary of the invention

[0004] The present invention provides a salt corrosion resistant admixture for marine engineering concrete. Through the joint action of multiple raw materials, on the one hand, from the perspective of improving the density of concrete, the multiple raw materials are blended and used to significantly improve the working performance of concrete and the internal density of concrete; on the other hand, from the perspective of physical and chemical reactions, some inhibitor materials are added to reduce the occurrence of corrosion reactions, thereby improving the ability of marine engineering concrete to resist harmful salt ions in seawater such as chloride ions and sulfate ions from entering the interior of concrete, reducing damage to marine engineering concrete specimens, and enabling the marine engineering concrete to have higher early and late strengths and excellent durability.

[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0006] The invention discloses an anti-salt corrosion admixture for marine engineering concrete, which is composed of the following raw materials in parts by weight: 40-60 parts of anti-corrosion agent, 20-30 parts of anti-seepage agent, 60-80 parts of mineral micro powder, 0.5-1 parts of filler, 1-3 parts of anti-corrosion auxiliary agent and 0.3-0.5 parts of water reducing agent.

[0007] Preferably, the corrosion resist is composed of modified polypropylene fiber and nano-organic montmorillonite in a mass ratio of 1:1.

[0008] Preferably, the modified polypropylene fiber is prepared by the following method: 20g of polypropylene fiber is soaked in 200ml of 4% by mass NaOH solution for 4h, then taken out, the surface is washed with deionized water, and then it is placed in styrene acrylic emulsion (emulsion: water = 1:1) and stirred and soaked for 30min, and then taken out and dried at 80°C; the length of the polypropylene fiber is 3-5mm.

[0009] Preferably, the anti-seepage agent is one of silicate cement or diatomaceous earth.

[0010] Preferably, the mineral powder is composed of barium slag and phosphorus slag in a mass ratio of 1:2; the content of soluble barium ions in the barium slag is not less than 5%.

[0011] Preferably, the filler is composed of nano-silicon dioxide and modified biochar in a mass ratio of 1:1; the particle size of the nano-silicon dioxide is 20-60nm.

[0012] Preferably, the modified biochar is prepared by the following method:

[0013] (1) adding the plant straw biochar prepared by high-temperature calcination to a 60°C NaOH solution, stirring and reacting for 2 hours, filtering, washing to neutral dryness to obtain the pretreated biochar for later use; the solid-liquid ratio of the plant straw biochar to the NaOH solution is 1 g:10 ml, and the concentration of the NaOH solution is 5 mol / L;

[0014] (2) Weigh 10 g of CaO powder, add it to 500 ml of deionized water, stir it magnetically for 6-8 hours to obtain a suspension, then slowly add 50 ml of 1 mol / L phosphoric acid solution, and adjust the pH of the solution to 10.0 with NaOH. After the addition is completed, continue to react for 2 hours, then filter and wash to neutrality, and dry at 80°C for 20 hours to obtain nano-hydroxyapatite;

[0015] (3) Soaking the pretreated biochar in a nano-hydroxyapatite suspension with a mass fraction of 5% for 2-3 hours under magnetic stirring, then filtering and washing to neutrality, and drying to obtain modified biochar; the solid-liquid ratio of the pretreated biochar to the nano-hydroxyapatite suspension is 1g:10ml.

[0016] Preferably, the anti-corrosion aid is composed of sodium dodecyl polyoxyethylene ether sulfonate and dimethylacetamide in a mass ratio of 0.6-0.8:1.

[0017] Preferably, the water reducer is one of a melamine water reducer and a naphthalene water reducer.

[0018] The present invention also provides a method for preparing the above-mentioned salt corrosion resistant admixture for marine engineering concrete, which comprises the following steps:

[0019] S1: Mix barium slag and phosphorus slag in a mass ratio of 1:2 and add them into a ball mill. Set the speed of the ball mill to 300 r / min and mill for 30 minutes to obtain mineral powder.

[0020] S2: Evenly mix the anti-corrosion agent, anti-seepage agent, filler, anti-corrosion aid, and water reducing agent with the mineral micro powder according to the mass ratio.

[0021] The designed dosage of the anti-salt corrosion admixture for marine engineering concrete prepared by the present invention is 3-5% of the mass of the concrete mortar.

[0022] Barium slag is the residual solid in the production of barium salts and is an industrial waste. With the development of my country's chemical industry, the amount of barium slag produced has increased year by year, and the cumulative accumulation has exceeded 10 million tons. Due to the low reusability and high cost of reuse of barium slag, the current treatment of barium slag mainly adopts the method of stockpiling. This not only occupies a large amount of land, but also pollutes the local environment. Moreover, with the erosion of rainwater, Ba 2+ It is easy to penetrate into the groundwater, making the groundwater 2+The content exceeds the standard, which directly has an adverse effect on organisms. The accumulation of a large amount of barium slag not only causes a waste of resources, but also causes complex physical and chemical reactions in the slag pile due to long-term exposure to the sun and rain, producing harmful gases such as sulfur dioxide and hydrogen sulfide, causing serious pollution to the atmosphere, soil, water resources, etc. Phosphorus slag is a product obtained by using phosphate ore, silica, and coke as raw materials. When yellow phosphorus is produced by an electric furnace method, a molten material is formed at a high temperature of 1400-1600°C, and then quenched with water. The main minerals of the slag are wollastonite, lanceolite, and calcium silicate. The main chemical components are CaO and SiO2, and it also contains a small amount of Al2O3, Fe2O3, MgO, P2O5, etc., and has a high potential activity. In the present invention, barium slag is compounded with phosphorus slag to form a mineral powder, in which the soluble Ba dissolved in the barium slag 2+ Can react with SO4 in seawater 2- Insoluble BaSO4 is formed, which can fill the tiny gaps in the concrete material, effectively reducing the porosity of the concrete material while also filling the invasion channels of harmful ions, reducing the corrosiveness of other salt ions; at the same time, the phosphorus slag and barium slag in the mineral micropowder contain a certain alkalinity. Under the synergistic effect of the anti-corrosion additives composed of sodium dodecyl polyoxyethylene ether sulfonate and dimethylacetamide, a suitable alkaline environment is provided for the concrete. The alkalinity of the pore solution in the concrete material is an important factor affecting the formation of sulfate corrosion products. Its alkaline components will gradually be released into the concrete pore solution. The alkaline pore solution environment will fundamentally inhibit the formation of concrete sulfate corrosion products such as calcium aluminate, thereby reducing the risk of concrete being attacked by sulfate.

[0023] The corrosion inhibitor of the invention contains two components, namely, modified polypropylene fiber and nano-organic montmorillonite. The two components work together to significantly improve the surface roughness of the modified polypropylene fiber, increase the specific surface area of ​​the fiber, improve the surface energy, and form good compatibility with the organic montmorillonite. By utilizing the excellent mechanical properties and dispersibility of the organic nano-montmorillonite, the modified polypropylene fiber forms good dispersibility inside the concrete, enhances the mechanical properties of the concrete, effectively inhibits the development of cracks, and improves the microscopic pore structure inside the concrete to a certain extent, thereby significantly improving the ability of the marine engineering concrete to resist the corrosion of salt ions. At the same time, the nano-organic montmorillonite also has good adsorption capacity, can better adsorb salt ions, and prevent salt ions such as chloride ions, sulfate ions, magnesium ions, etc. from entering the concrete to cause corrosion to the concrete structure.

[0024] The filler composed of modified biochar and nano-silicon dioxide is adopted. On the one hand, the modified biochar has a cross-linked network structure that can adsorb more nano-silicon dioxide to the surface, and the strong combination promotes each other, jointly promoting the formation of CSH active groups in the cement hydration process, significantly improving the strength of concrete, and on the other hand, the cross-linked network structure is filled in the tiny pores of the material, which can better improve the density of concrete, thereby effectively reducing the comprehensive erosion of various salts in seawater. The filler of the present invention and the anti-corrosion additive complement each other, the high activity characteristics of the nanoparticles enhance the dispersibility of the anti-corrosion additive in concrete, and the anti-corrosion additive significantly enhances the adsorption and filling properties of the nanoparticles, effectively reducing the erosion of various salts in marine engineering concrete in the complex marine environment.

[0025] The beneficial effects of the present invention are:

[0026] 1) The mineral powder of the present invention is compounded with solid waste barium slag and phosphorus slag, which improves the comprehensive utilization rate of solid waste. At the same time, the mineral powder and the anti-corrosion additive work together to fundamentally inhibit the generation of concrete sulfate corrosion products such as ettringite, thereby reducing the risk of marine concrete being corroded by sulfate in seawater.

[0027] 2) The corrosion inhibitor of the present invention has a synergistic effect, can effectively fill the micropores inside the concrete, improve the density inside the concrete, and can also better adsorb salt ions, prevent salt ions such as chloride ions, sulfate ions, magnesium ions, etc. from entering the concrete to corrode the concrete structure, thereby playing a good corrosion resistance role.

[0028] 3) Multiple raw materials work together and complement each other. On the one hand, they improve the density of the marine concrete material, thereby improving the ability to resist the entry of harmful ions such as chloride ions and sulfate ions; on the other hand, they reduce the risk of marine concrete being corroded by salt by inhibiting the occurrence of corrosion reactions. At the same time, the prepared marine concrete has higher strength and excellent durability. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto. Unless otherwise specified, the raw materials used in the present invention are all commercially available, wherein the barium slag is obtained from a barium salt manufacturer in Hebei Province, and its main components are shown in Table 1 below; the phosphorus slag is purchased from a yellow phosphorus manufacturer in Sichuan Province, and its density is 2.98 g / cm 3 , with a specific surface area of ​​420m 2 / kg.

[0030] Table 1 Main components of barium slag

[0031]

[0032] Example 1

[0033] The invention discloses an anti-salt corrosion admixture for marine engineering concrete, which is composed of the following raw materials in parts by weight: 40 parts of anti-corrosion agent, 20 parts of anti-seepage agent, 60 parts of mineral micro powder, 0.5 parts of filler, 1 part of anti-corrosion auxiliary agent and 0.3 parts of water reducing agent.

[0034] The anti-corrosion agent modified polypropylene fiber and the nano organic montmorillonite are composed in a mass ratio of 1:1.

[0035] The modified polypropylene fiber is prepared by the following method: 20g of polypropylene fiber is soaked in 200ml of 4% by mass NaOH solution for 4 hours, then taken out, the surface is washed with deionized water, and then it is put into styrene acrylic emulsion (emulsion: water = 1:1) and stirred and soaked for 30 minutes, and then taken out and dried at 80°C to obtain the obtained polypropylene fiber; the length of the polypropylene fiber is 3-5mm.

[0036] The anti-seepage agent is one of silicate cement and diatomaceous earth.

[0037] The mineral powder is composed of barium slag and phosphorus slag in a mass ratio of 1:2; the content of soluble barium ions in the barium slag is not less than 5%.

[0038] The filler is composed of nano silicon dioxide and modified biochar in a mass ratio of 1:1; the particle size of the nano silicon dioxide is 20-60nm.

[0039] The modified biochar is prepared by the following method:

[0040] (1) adding the plant straw biochar prepared by high-temperature calcination to a 60°C NaOH solution, stirring and reacting for 2 hours, filtering, washing to neutral dryness to obtain the pretreated biochar for later use; the solid-liquid ratio of the plant straw biochar to the NaOH solution is 1 g:10 ml, and the concentration of the NaOH solution is 5 mol / L;

[0041] (2) Weigh 10 g of CaO powder, add it to 500 ml of deionized water, stir it magnetically for 6-8 hours to obtain a suspension, then slowly add 50 ml of 1 mol / L phosphoric acid solution, and adjust the pH of the solution to 10.0 with NaOH. After the addition is completed, continue to react for 2 hours, then filter and wash to neutrality, and dry at 80°C for 20 hours to obtain nano-hydroxyapatite;

[0042] (3) Soaking the pretreated biochar in a nano-hydroxyapatite suspension with a mass fraction of 5% for 2-3 hours under magnetic stirring, then filtering and washing to neutrality, and drying to obtain modified biochar; the solid-liquid ratio of the pretreated biochar to the nano-hydroxyapatite suspension is 1g:10ml.

[0043] The anti-corrosion aid is composed of sodium dodecyl polyoxyethylene ether sulfonate and dimethylacetamide in a mass ratio of 0.6:1.

[0044] The water reducer is one of a melamine water reducer and a naphthalene water reducer.

[0045] The present invention also provides a method for preparing the above-mentioned salt corrosion resistant admixture for marine engineering concrete, which comprises the following steps:

[0046] S1: Mix barium slag and phosphorus slag in a mass ratio of 1:2 and add them into a ball mill. Set the speed of the ball mill to 300 r / min and mill for 30 minutes to obtain mineral powder.

[0047] S2: Evenly mix the anti-corrosion agent, anti-seepage agent, filler, anti-corrosion aid, and water reducing agent with the mineral micro powder according to the mass ratio.

[0048] Example 2

[0049] The invention discloses an anti-salt corrosion admixture for marine engineering concrete, which is composed of the following raw materials in parts by weight: 60 parts of corrosion inhibitor, 30 parts of seepage prevention agent, 80 parts of mineral micro powder, 1 part of filler, 3 parts of corrosion inhibitor and 0.5 parts of water reducing agent.

[0050] The anti-corrosion agent modified polypropylene fiber and the nano organic montmorillonite are composed in a mass ratio of 1:1.

[0051] The modified polypropylene fiber is prepared by the following method: 20g of polypropylene fiber is soaked in 200ml of 4% by mass NaOH solution for 4 hours, then taken out, the surface is washed with deionized water, and then it is put into styrene acrylic emulsion (emulsion: water = 1:1) and stirred and soaked for 30 minutes, and then taken out and dried at 80°C to obtain the obtained polypropylene fiber; the length of the polypropylene fiber is 3-5mm.

[0052] The anti-seepage agent is one of silicate cement and diatomaceous earth.

[0053] The mineral powder is composed of barium slag and phosphorus slag in a mass ratio of 1:2; the content of soluble barium ions in the barium slag is not less than 5%.

[0054] The filler is composed of nano silicon dioxide and modified biochar in a mass ratio of 1:1; the particle size of the nano silicon dioxide is 20-60nm.

[0055] The modified biochar is prepared by the following method:

[0056] (1) adding the plant straw biochar prepared by high-temperature calcination to a 60°C NaOH solution, stirring and reacting for 2 hours, filtering, washing to neutral dryness to obtain the pretreated biochar for later use; the solid-liquid ratio of the plant straw biochar to the NaOH solution is 1 g:10 ml, and the concentration of the NaOH solution is 5 mol / L;

[0057] (2) Weigh 10 g of CaO powder, add it to 500 ml of deionized water, stir it magnetically for 6-8 hours to obtain a suspension, then slowly add 50 ml of 1 mol / L phosphoric acid solution, and adjust the pH of the solution to 10.0 with NaOH. After the addition is completed, continue to react for 2 hours, then filter and wash to neutrality, and dry at 80°C for 20 hours to obtain nano-hydroxyapatite;

[0058] (3) Soaking the pretreated biochar in a nano-hydroxyapatite suspension with a mass fraction of 5% for 2-3 hours under magnetic stirring, then filtering and washing to neutrality, and drying to obtain modified biochar; the solid-liquid ratio of the pretreated biochar to the nano-hydroxyapatite suspension is 1g:10ml.

[0059] The anti-corrosion aid is composed of sodium dodecyl polyoxyethylene ether sulfonate and dimethylacetamide in a mass ratio of 0.8:1.

[0060] The water reducer is one of a melamine water reducer and a naphthalene water reducer.

[0061] The present invention also provides a method for preparing the above-mentioned salt corrosion resistant admixture for marine engineering concrete, which comprises the following steps:

[0062] S1: Mix barium slag and phosphorus slag in a mass ratio of 1:2 and add them into a ball mill. Set the speed of the ball mill to 300 r / min and mill for 30 minutes to obtain mineral powder.

[0063] S2: Evenly mix the anti-corrosion agent, anti-seepage agent, filler, anti-corrosion aid, and water reducing agent with the mineral micro powder according to the mass ratio.

[0064] Example 3

[0065] The invention discloses an anti-salt corrosion admixture for marine engineering concrete, which is composed of the following raw materials in parts by weight: 50 parts of corrosion inhibitor, 25 parts of seepage prevention agent, 70 parts of mineral micro powder, 0.8 parts of filler, 2 parts of corrosion inhibitor and 0.4 parts of water reducing agent.

[0066] The anti-corrosion agent modified polypropylene fiber and the nano organic montmorillonite are composed in a mass ratio of 1:1.

[0067] The modified polypropylene fiber is prepared by the following method: 20g of polypropylene fiber is soaked in 200ml of 4% by mass NaOH solution for 4 hours, then taken out, the surface is washed with deionized water, and then it is put into styrene acrylic emulsion (emulsion: water = 1:1) and stirred and soaked for 30 minutes, and then taken out and dried at 80°C to obtain the obtained polypropylene fiber; the length of the polypropylene fiber is 3-5mm.

[0068] The anti-seepage agent is one of silicate cement and diatomaceous earth.

[0069] The mineral powder is composed of barium slag and phosphorus slag in a mass ratio of 1:2; the content of soluble barium ions in the barium slag is not less than 5%.

[0070] The filler is composed of nano silicon dioxide and modified biochar in a mass ratio of 1:1; the particle size of the nano silicon dioxide is 20-60nm.

[0071] The modified biochar is prepared by the following method:

[0072] (1) adding the plant straw biochar prepared by high-temperature calcination to a 60°C NaOH solution, stirring and reacting for 2 hours, filtering, washing to neutral dryness to obtain the pretreated biochar for later use; the solid-liquid ratio of the plant straw biochar to the NaOH solution is 1 g:10 ml, and the concentration of the NaOH solution is 5 mol / L;

[0073] (2) Weigh 10 g of CaO powder, add it to 500 ml of deionized water, stir it magnetically for 6-8 hours to obtain a suspension, then slowly add 50 ml of 1 mol / L phosphoric acid solution, and adjust the pH of the solution to 10.0 with NaOH. After the addition is completed, continue to react for 2 hours, then filter and wash to neutrality, and dry at 80°C for 20 hours to obtain nano-hydroxyapatite;

[0074] (3) Soaking the pretreated biochar in a nano-hydroxyapatite suspension with a mass fraction of 5% for 2-3 hours under magnetic stirring, then filtering and washing to neutrality, and drying to obtain modified biochar; the solid-liquid ratio of the pretreated biochar to the nano-hydroxyapatite suspension is 1g:10ml.

[0075] The anti-corrosion aid is composed of sodium dodecyl polyoxyethylene ether sulfonate and dimethylacetamide in a mass ratio of 0.7:1.

[0076] The water reducer is one of a melamine water reducer and a naphthalene water reducer.

[0077] The present invention also provides a method for preparing the above-mentioned salt corrosion resistant admixture for marine engineering concrete, which comprises the following steps:

[0078] S1: Mix barium slag and phosphorus slag in a mass ratio of 1:2 and add them into a ball mill. Set the speed of the ball mill to 300 r / min and mill for 30 minutes to obtain mineral powder.

[0079] S2: Evenly mix the anti-corrosion agent, anti-seepage agent, filler, anti-corrosion aid, and water reducing agent with the mineral micro powder according to the mass ratio.

[0080] Comparative Example 1

[0081] A salt corrosion resistant admixture for marine engineering concrete, whose raw material composition and preparation method are basically the same as those in Example 3, except that the corrosion resistant agent is composed of unmodified polypropylene fiber and nano-organic montmorillonite in a mass ratio of 1:1.

[0082] Comparative Example 2

[0083] A salt corrosion resistant admixture for marine engineering concrete, whose raw material composition and preparation method are basically the same as those in Example 3, the only difference being that it does not contain an anti-corrosion additive component.

[0084] Comparative Example 3

[0085] A salt corrosion resistant admixture for marine engineering concrete, whose raw material composition and preparation method are basically the same as those in Example 3, except that the corrosion resistant additive is sodium dodecyl polyoxyethylene ether sulfonate.

[0086] Comparative Example 4

[0087] A salt corrosion resistant admixture for marine engineering concrete, whose raw material composition and preparation method are basically the same as those in Example 3, the only difference is that the corrosion resistant additive is dimethylacetamide.

[0088] Comparative Example 5

[0089] A salt corrosion resistant admixture for marine engineering concrete, whose raw material composition and preparation method are basically the same as those in Example 3, the only difference being that the filler is composed of nano-silicon dioxide and unmodified biochar in a mass ratio of 1:1.

[0090] Comparative Example 6

[0091] A salt corrosion resistant admixture for marine engineering concrete, whose raw material composition and preparation method are basically the same as those in Example 3, the only difference being that the filler is nano-silicon dioxide.

[0092] Comparative Example 7

[0093] A salt corrosion resistant admixture for marine engineering concrete, whose raw material composition and preparation method are basically the same as those in Example 3, the only difference being that the filler is modified biochar.

[0094] Performance Testing

[0095] The marine concrete anti-salt corrosion admixture prepared in Examples 1-3 and Comparative Examples 1-7 of the present invention was used to prepare mortar according to 5% (wt) of the marine concrete adhesive, and the performance of the mortar was tested respectively, wherein the marine silicate cement was composed of the following raw materials in weight percentage: 35% silicate cement clinker, 25% fly ash, 27% slag powder, 10% gypsum, and 3% silica fume; its performance index met the requirements of the national standard GB / T 31289-2014 "Marine silicate cement". The test method refers to JGJ / T70-2009 "Standard for Basic Performance Test Methods of Building Mortar" and JC / T1011-2021 "Concrete Anti-Corrosion Preservative", and the specific performance test results are shown in Table 2.

[0096] Table 2 Performance test results

[0097]

[0098] From the above data, it can be seen that after the anti-salt corrosion admixture for marine engineering concrete prepared by Examples 1-3 of the present invention is added to concrete, its expansion coefficient and chloride ion diffusion coefficient are significantly reduced, and the corrosion resistance coefficient, 7-day compressive strength and 28-day compressive strength are significantly improved. This shows that after the anti-salt corrosion admixture for marine engineering concrete prepared by the present invention is used, it can effectively fill the internal micropores of concrete and improve the internal density of concrete. At the same time, it can also better adsorb salt ions, prevent chloride ions, sulfate ions, magnesium ions and other salt ions from entering the concrete to cause corrosion to the concrete structure, and play a good anti-corrosion role. The prepared marine engineering concrete has high strength and excellent durability, which prolongs the service life of concrete. Compared with Comparative Examples 1-7, the effect of the embodiments of the present invention is significantly better than that of the comparative examples, which shows that the raw materials of the present invention interact with each other, and changing any type or ratio of raw materials cannot achieve the effect of the present invention.

[0099] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A salt corrosion resistant admixture for marine engineering concrete, which is characterized by: The invention is composed of the following raw materials in parts by weight: 40-60 parts of corrosion inhibitor, 20-30 parts of seepage prevention agent, 60-80 parts of mineral micro powder, 0.5-1 parts of filler, 1-3 parts of corrosion inhibitor, and 0.3-0.5 parts of water reducing agent; the filler is composed of nano silicon dioxide and modified biochar in a mass ratio of 1:1; the particle size of the nano silicon dioxide is 20-60nm; The modified biochar is prepared by the following method: (1) adding the plant straw biochar prepared by high-temperature calcination to a 60°C NaOH solution, stirring and reacting for 2 hours, filtering, washing to neutral dryness to obtain the pretreated biochar for later use; the solid-liquid ratio of the plant straw biochar to the NaOH solution is 1 g:10 ml, and the concentration of the NaOH solution is 5 mol / L; (2) Weigh 10 g of CaO powder, add it to 500 ml of deionized water, stir it magnetically for 6-8 hours to obtain a suspension, then slowly add 50 ml of 1 mol / L phosphoric acid solution, and adjust the pH of the solution to 10.0 with NaOH. After the addition is completed, continue to react for 2 hours, then filter and wash to neutrality, and dry at 80°C for 20 hours to obtain nano-hydroxyapatite; (3) Soaking the pretreated biochar in a nano-hydroxyapatite suspension with a mass fraction of 5% for 2-3 hours under magnetic stirring, then filtering and washing to neutrality, and drying to obtain modified biochar; the solid-liquid ratio of the pretreated biochar to the nano-hydroxyapatite suspension is 1g:10ml.

2. The salt corrosion resistant admixture for marine engineering concrete according to claim 1, characterized in that: The anti-corrosion agent is composed of modified polypropylene fiber and nano-organic montmorillonite in a mass ratio of 1:

1.

3. The salt corrosion resistant admixture for marine engineering concrete according to claim 2, characterized in that: The modified polypropylene fiber is prepared by the following method: 20g of polypropylene fiber is soaked in 200ml of 4% by mass NaOH solution for 4 hours, then taken out, the surface is washed with deionized water, and then it is placed in styrene acrylic emulsion and stirred and soaked for 30 minutes, and then taken out and dried at 80°C to obtain the obtained fiber; the length of the polypropylene fiber is 3-5mm.

4. The salt corrosion resistant admixture for marine engineering concrete according to claim 1, characterized in that: The anti-seepage agent is one of silicate cement and diatomaceous earth.

5. The salt corrosion resistant admixture for marine engineering concrete according to claim 1, characterized in that: The mineral powder is composed of barium slag and phosphorus slag in a mass ratio of 1:2; the content of soluble barium ions in the barium slag is not less than 5%.

6. The salt corrosion resistant admixture for marine engineering concrete according to claim 1, characterized in that: The anti-corrosion aid is composed of sodium dodecyl polyoxyethylene ether sulfonate and dimethylacetamide in a mass ratio of 0.6-0.8:

1.

7. The salt corrosion resistant admixture for marine engineering concrete according to claim 1, characterized in that: The water reducer is one of a melamine water reducer and a naphthalene water reducer.

8. A method for preparing the salt corrosion resistant admixture for marine engineering concrete according to any one of claims 1 to 7, characterized in that: It includes the following steps: S1: Mix barium slag and phosphorus slag in a mass ratio of 1:2 and add them into a ball mill. Set the speed of the ball mill to 300 r / min and mill for 30 minutes to obtain mineral powder. S2: Evenly mix the anti-corrosion agent, anti-seepage agent, filler, anti-corrosion aid, and water reducing agent with the mineral micro powder according to the mass ratio.

Citation Information

Patent Citations

  • Preparation method of expanded perlite composite modified thermal insulation material

    CN108424099A

  • Salt-erosion-resistant marine concrete admixture and preparation method thereof

    CN112745054A

  • Composite coagulation-accelerating anticorrosive material and preparation method thereof

    CN116462442A